Devices operability control through gas supply system mode parameter routine measurement history. (January 2023) - Sukharev, Mikhail G.; Chupin, Maksim
Abstract: Effective control of pipeline systems requires adequate mathematical models. To match an object with the model it is necessary to analyze data on physical system structure and parameters and on operating processes (or the fluid flow regimes). Operating parameter measurements serve as data source for operational control. Incorrect SCADA readings bring about erroneous simulation results and unfounded dispatch decisions. Sometimes it is rather easy to identify information system failures and tell the cause. But sometimes as in the case of stage-by-stage failure such as sensor drift failure identification becomes really difficult. To detect and eliminate a progressive defect it is advisable to use maximum of available data, that is all measurements of the operating parameters (pressure, flow rate and, possibly, temperature) transmitted during the last few SCADA sessions. This approach takes into account the interdependence of operating parameters within the same session as well as specific parameter measurements during a number of sessions. The suggested model of identifying the failed device and the failure moment is built on a stochastic basis. The measurement results are considered random variables, which distribution obeys error theory standard assumptions. Highlights: Information processing on a set of the operating parameters measurements of the pipeline system. Models for failures recognizing of pressure gauges and flow meters. Determination of the failure moment and place at the metrological complex. Potential applicability of the methodology to unaccounted for gas.